COUNTER-HEGEMONY DALAM SATIRE: Analisis Wacana Kritis Konten YouTube Tretan Muslim - Nahumarury, Fahrul Arif; Arief, Maulana (Sintesa, 2025)
This research discusses counter-hegemony in satire within the content "Jual Beli Air Doa Para Habib with Guru Gembul – OFFSIDE BERAGAMA," produced by Tretan Muslim on the YouTube channel Tretan Universe. In this content, Tretan Muslim and Guru Gembul use satire and humor as their approach. This study employs a qualitative critical paradigm with a critical discourse analysis method by Norman Fairclough, which enables the researcher to explore how language and symbols in the video construct meaning and create narratives in the satire. YouTube has become a new space for society to access and simultaneously reconstruct religious discourse. The findings from the discourse include mystic rituals in religion, social and health critique discourses, marketing strategy discourse, mystic rituals and local culture, the commodification of religion through the sale of blessings, the legitimization of power through relics, and the discourse of discussion spaces. This research demonstrates that satire is not only a form of entertainment but also a form of resistance (counter-hegemony) against the commercialization of religion. Through satire, humor, and visual symbols, Tretan Muslim and Guru Gembul critique the practice of selling prayer water that misuses religious symbols for various interests. Keywords : Counter-hegemoni; Satire; Critical Discourse Analysis; Commercialization of Religion;